Rice caryopsis- Its nutritive value and medicinal properties: Its nutritive value and medicinal properties - Nayak, Ajanta; Das, Kaushik (ORYZA-An International Journal of Rice, 2024)
Cereal crops like rice provides food and sustain health in animal consumers. Its edible caryopsis beside being a source of energy also act as the main nutritional foundation especially for mankind. This paper reviewed the structural complexity of caryopsis, distribution pattern of various nutrients present and their medicinal properties. The caryopsis layers are rich in carbohydrates, proteins, amino acids, lipids, minerals, vitamins, dietary fiber and bioactive compounds. But industrial milling removes most of these nutrient components as polished white rice is mostly consumed. Dismal grain filling process and gradual decreasing of nutrients in grains of many rice cultivars are other factors which further worsen grain quality and deprive poor consumers from getting adequate nutritive value. It results in micronutrient deficiencies, malnutrition and chronic diseases which seriously influence the human health. Therefore, here we have discussed various strategies which will help in mitigating the global health issues. Besides improving human health this review may further help in fulfilling growing demand for quality rice, educating consumers about diet and making them health conscious so that health promoting nutritious brown caryopsis is given more preference rather than the polished endosperm.